2016
DOI: 10.1071/an15082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a short-term prepartum supplementation on beef cows and calves’ performance in pastoral conditions

Abstract: Multiparous Aberdeen Angus · Hereford crossbred cows were used to evaluate the effect of supplementation during the last month of gestation on milk production and composition and cow and calf performance. Cows were assigned randomly to supplement (SUP; n = 18) or Control (CON; n = 17) treatments. Supplemented cows were offered (1 kg/100 kg bodyweight) a mix of sorghum grain and protein concentrated (67 : 33 as-fed basis; 16% crude protein, 11% acid detergent fibre) from (mean AE s.e.m.) 33 AE 1.4 days prepartu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…It is also possible that the prepartum nutrition plan affects oocyte quality (Krisher, 2004), size, and steriodogenic capacity of the corpus luteum, and uterine function through mechanisms that cause extended anestrus (Lucy, 2003), all of these mechanisms resulting in an improved reproductive outcome. Our results are in agreement with those of other authors who reported benefits on reproduction when primiparous (Wiley et al, 1991;Soto et al, 2001) or multiparous (Quintans et al, 2016) cows were well fed or supplemented before calving. However, Stalker et al (2006) did not find a positive impact of prepartum supplementation on pregnancy rates.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is also possible that the prepartum nutrition plan affects oocyte quality (Krisher, 2004), size, and steriodogenic capacity of the corpus luteum, and uterine function through mechanisms that cause extended anestrus (Lucy, 2003), all of these mechanisms resulting in an improved reproductive outcome. Our results are in agreement with those of other authors who reported benefits on reproduction when primiparous (Wiley et al, 1991;Soto et al, 2001) or multiparous (Quintans et al, 2016) cows were well fed or supplemented before calving. However, Stalker et al (2006) did not find a positive impact of prepartum supplementation on pregnancy rates.…”
Section: Discussionsupporting
confidence: 93%
“…An additional advantage of short supplementation period of less than 75 days before calving is that it seems not to influence calf birth weight (Wiley et al, 1991;Bellows et al, 2001;Soto et al, 2001;Alexander et al, 2002;Scarsi, 2012;Quintans et al, 2016). Indeed, in the present experiment, calves' weight at calving was not influenced by supplementation, and no difficulties at calving were observed.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Mainly, when low-quality forages are not limited by quantity, protein supplements are considered the main limiting nutrient (DelCurto et al, 2000). In fact, protein supplementation for beef cows fed tropical forages has a positive effect on forage dry-matter intake, digestibility, nutrient concentration in the rumen, crude protein (CP) intake, BW, BCS, blood metabolites and reproductive performance (da Silva et al, 2017;Quintans et al, 2016;Wilson et al, 2016a).…”
Section: General Introductionmentioning
confidence: 99%